2016
DOI: 10.1159/000443635
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of Muscle Regeneration and Adaptation to Advance Muscle Tissue Regeneration Strategies

Abstract: Skeletal muscle has an exceptional ability to regenerate and adapt following injury. Tissue engineering approaches (e.g. cell therapy, scaffolds, and pharmaceutics) aimed at enhancing or promoting muscle regeneration from severe injuries are a promising and active field of research. Computational models are beginning to advance the field by providing insight into regeneration mechanisms and therapies. In this paper, we summarize the contributions computational models have made to understanding muscle remodelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 88 publications
0
33
0
Order By: Relevance
“…For example, previous computational models have demonstrated that simultaneous targeting of multiple cells types rather than fibroblasts alone can enhance the efficacy of therapies for pulmonary fibrosis (Warsinske et al, 2016). Inflammatory cells, including macrophages and neutrophils, will be incorporated into a model of post-MI wound healing as the primary source and modulators of inflammatory cytokines and TGFβ input, as has been demonstrated previously in simulations of skeletal muscle and lung fibrosis (Martin et al, 2016;Warsinske et al, 2016;Virgilio et al, 2018). This will add another layer of complexity to the spatial heterogeneity of the coupled model by representing cytokine production from individual cells, diffusion of soluble cytokines and growth factors, and migration that is driven by chemokine gradients.…”
Section: State Of the Multiscale Modeling Field And Contributions Of mentioning
confidence: 98%
“…For example, previous computational models have demonstrated that simultaneous targeting of multiple cells types rather than fibroblasts alone can enhance the efficacy of therapies for pulmonary fibrosis (Warsinske et al, 2016). Inflammatory cells, including macrophages and neutrophils, will be incorporated into a model of post-MI wound healing as the primary source and modulators of inflammatory cytokines and TGFβ input, as has been demonstrated previously in simulations of skeletal muscle and lung fibrosis (Martin et al, 2016;Warsinske et al, 2016;Virgilio et al, 2018). This will add another layer of complexity to the spatial heterogeneity of the coupled model by representing cytokine production from individual cells, diffusion of soluble cytokines and growth factors, and migration that is driven by chemokine gradients.…”
Section: State Of the Multiscale Modeling Field And Contributions Of mentioning
confidence: 98%
“…Systems biology has been used to study a wide array of topics 52 including systems pharmacology, 4,10,20 vascular and muscle growth, 34 or cancer development and therapy. 7,14,53 Computational modeling and systems biology approaches can help integrate large sets of data and provide additional biological insights, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory cell ordinary differential equation. The inflammatory cell dynamics were defined based on previous work by Martin et al (49,50). Our goal was to reduce the computational cost of the ABM but still retain the dynamic behaviors of the inflammatory cells that were previously established.…”
Section: Methodsmentioning
confidence: 99%